Analysis of the Ability of Islamic Banking Students of the Islamic Faculty of Economics and Business IAIN Lhokseumawe in Writing Skills of Scientific Papers - Muhammad Syafril Nasution (Global Writing Academica Researching & Publishing, 2023)
Scientific work is an integral part of the academic circle, because scientific work is the main task and is a prerequisite for all study programs and degrees. Scientific work is a benchmark for academics in the application of scientific knowledge. In final year students, there are still many of them experiencing problems when working on writing their final assignment, namely a thesis. This research was conducted to find out how the ability to write scientific papers, especially in writing thesis, among Islamic Banking students of FEBI IAIN Lhokseumawe who have finished taking research methods courses. The results of the research, students' ability to write scientific papers is described in three forms. First, the ability to write scientific article systematics as many as 73 students or 86% is categorized as good or able to write scientific article systematics. The remaining 13 students or 14% are categorized as needing guidance. Second, students' ability to write scientific articles. The contents of writing titles, author names, abstracts, research methods, and student bibliography are categorized as good because more than 75% can write. The rest, in preliminary writing, research results, discussion, conclusions and suggestions, students are categorized as needing guidance because only 25% can write well. Third, the ability to use Indonesian spelling. Several errors were found, which need attention, namely errors in capital letters, italics, periods, commas, and standard words. This error, because students do not read scientific papers, so that knowledge of the use of Indonesian spelling is still relatively lacking.